A via dos leucotrienos contribui para os efeitos antiinflamatórios do treinamento físico aeróbio na asma? - Custódio, Ricardo Wesley Alberca (2015)
Leukotrienes (LTs) play a central role in the pathophysiology of asthma. Aerobic exercise has been shown to be capable of reducing asthmatic inflammation. Therefore, this study investigated whether the anti-inflammatory effects of aerobic exercise are due to inhibition of the pathway of LTs. Forty BALB / c mice were divided into four groups: Control, Exercise, OVA and OVA + Exercise. The mice were sensitized and challenged with ovalbumin. Aerobic training was performed on a adapted treadmill, at low intensity, 5x / week, 1h / session for 4 weeks, after the establishment of airway inflammation. Total and differential cells were analized in bronchoalveolar lavage (BAL), cytokine levels in BAL, the number of lymphocytes and macrophages in the airway wall, the airway remodeling (collagen and elastic fibers, mucous production and thickness of bronchial smooth muscle), bronchial hyperresponsiveness, beyond the levels of leukotriene B4 (LTB4) and leukotriene C4 (LTC4) in BAL. In addition, immunohistochemistry was performed for 5-lipoxygenase (5-LO) LTA4 hydrolase (LTA4H) CysLT1 receptor, CysLT2 receptor, LTC4 synthase, LTB4 receptor 2 (BLT2). The results demonstrated that aerobic exercise reduced the total number of cells (p <0.05), eosinophils (p <0.05), neutrophils (p <0.001), lymphocytes (p <0.001) and macrophage (p <0.01) in BAL and the number of lymphocytes (p <0.05) and macrophages (p <0.01) in the airway wall. In addition, the accumulation of collagen fibers (p <0.01), elastic fibers (p <0.01) and mucus production (p <0.01) and the thickness of bronchial smooth muscle (P <0.05) and bronchial hyperresponsiveness levels at 25 MCh (p <0.05) and 50 MCh (p <0.01) were reduced in mice sensitized and trained. Furthermore, BAL IL-5 (p <0.05) were reduced, and the levels of LTB4 (p <0.05). The expression of 5-LO (p <0.05) LTA4H (p <0.05), the CysLT 1 receptor (p <0.05), CysLT 2 receptor (p <0.05), LTC4 synthase (p <0.05) and BLT2 (p <0.05) in peribronchial leukocytes were reduced by exercise and expression of 5-LO (p <0.05) LTA4H (p <0.05), the CysLT 1 receptor (p <0.05), CysLT 2 receptor (p <0.05), LTC4 synthase (p <0.05) and BLT2 (p <0.05) in the bronchial epithelium. We conclude that the low intensity aerobic exercise reduces phenotype of asthma by inhibiting the leukotriene pathway.